“Ensayo para el control de insectos con extractos de huaca (clibadium sp schultz) que atacan al caupí (vigna unguiculata L walp) en el Bajo Mayo- San Martín” - Azang Huaman, Pompilio (2002)
The struggle against the insects and diseases that destroy the cultivation is permanent and very ancient, this destruction that accomplish This about a third of the products potentially haversted and the regulation with chemical products is generating problems in the human health, in the environment and in the economy of the farmer. This situation compels to recapture and potentiality alternativa technologies that they can substituta the pesticidas synthetic. lt is as soon as in the present investigation work was determinad which is the most adequate concentration of extracts of Huaca ( Clibadium sp Schultz ) for the control of insects of caupí ( Vigna unguiculata L Walp) in field conditions, being the most encouraging result the treatment T5(1.6% of solution extract of "Huaca"). Also with this work is developed the Benefit analysis - Cost of the different treatments being the most beneficia! the treatment T6 ( Cipermetrina 0.7%) the one which is not agreed to the conservation of the environment and of the nature. Within these technologies, one of them is the use of vegetable extracts as traditional method that requires be potentiality to take advantage their/its benefits. The Peruvian Jungle counts on a diversity of plants with potential pesticidas is as soon as in the Region San Martin count on the "Huaca" (Clibadium sp Schultz ) , plant that grows in the scrubs, in the trails and in the banana crops ancient, with the one which was accomplished the present study. With the present work accomplished in the Community of Alone was observad the effects of the 'Huaca11 ( Clibadium sp Schultz ) in various concentrations in the control of insects ( Cicadelidos y Diabroticas ) of the caupí in field conditions.